ChemInform Abstract: Recent Developments in Radiolabeled Peptides for PET Imaging of Cancer. Issue 42 (September 2016) - Charron, Carlie L.; Farnsworth, Ashleigh L.; Roselt, Peter D.; Hicks, Rodney J.; Hutton, Craig A.
Abstract: Review: 91 refs.